Exploring stakeholders’ perceptions and priorities in promoting social sustainability through building design and public participation: a case study in Malaysia - Jhun, Ng Kean; Shari, Zalina; Hassan, Mohammad Mujaheed (Taylor and Francis, 2025)
This study aims to enhance stakeholder participation in public facility design to foster socially sustainable urban environments. Addressing gaps in public participation frameworks, it explores how increased engagement can improve social sustainability within Malaysia’s unique socio-political context. Using a qualitative approach with purposive sampling, in-depth interviews were conducted with 24 stakeholders, including industry experts, policymakers, and the public, to gather insights on current practices, challenges, and participation effectiveness in fostering social sustainability. Findings reveal low public participation due to insufficient political will and guidance. Key recommendations include improving communication, transparency, government support, and streamlining procedures. The study highlights stakeholder perspectives on socially sustainable development, emphasising community needs, continuous facility use, and accessibility. These insights provide valuable guidance for policymakers, practitioners, and researchers aiming to strengthen public participation and advance sustainable urban development in Malaysia.